1997
DOI: 10.1021/ac9703111
|View full text |Cite
|
Sign up to set email alerts
|

Multielemental Chemical Imaging Using Laser-Induced Breakdown Spectrometry

Abstract: Multichannel laser-induced breakdown spectrometry (LIBS) is used to generate selective chemical images for silver, titanium, and carbon from silicon photovoltaic cells. A 2.5 mJ pulsed nitrogen laser and a spectrometer using charge-coupled device detection were employed. LIBS images were acquired sequentially by moving the sample located on a motorized x-y translational stage step by step while storing the multichannel LIBS spectrum for each position of the sample, followed by computer-based reconstruction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…15,16 Rapid in situ analysis of worked material without sample preparation and micro-and macromapping over several centimetres by scanning the optical system or moving the sample on a translation stage are interesting capabilities of LIBS. 17,18 The sulphur content in steel was determined by the LIBS method. 19 The technique has been applied also for direct analysis of the carbon content in steel.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Rapid in situ analysis of worked material without sample preparation and micro-and macromapping over several centimetres by scanning the optical system or moving the sample on a translation stage are interesting capabilities of LIBS. 17,18 The sulphur content in steel was determined by the LIBS method. 19 The technique has been applied also for direct analysis of the carbon content in steel.…”
Section: Introductionmentioning
confidence: 99%
“…Laserna et al have demonstrated the capability of LIBS as a tool for the characterization of metal impurities (Ag, Ti, Al, and Cu), calcium, phosphorous and carbon for different silicon grades [10][11][12][13]. However boron impurities in silicon have up to now been measured only using Glow Discharge Mass Spectrometry (GDMS) and Inductively Coupled Plasma (ICP) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Sequential laser pulses on the same spot provide information on depth profiling of the materials. In the last decade, variety of applications concerning LIBS depth profiling with nanosecond and femtosecond lasers has been performed [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%